2020
DOI: 10.1128/iai.00046-20
|View full text |Cite
|
Sign up to set email alerts
|

Human IgM Inhibits the Formation of Titan-Like Cells in Cryptococcus neoformans

Abstract: Human studies have shown associations between cryptococcal meningitis and reduced IgM memory B cell levels, and studies in IgM- and/or B cell-deficient mice have demonstrated increased Cryptococcus neoformans dissemination from lungs to brain. Since immunoglobulins are part of the immune milieu that C. neoformans confronts in a human host, and its ability to form titan cells is an important virulence mechanism, we determined the effect of human immunoglobulins on C. neoformans titan cell formation in vitro. (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Moreover, our data also highlight an important role of the B-1 cells during chronic infection, as seen by the higher IgM antibody titer compared with the antigen-specific IgG antibody titer between the XID and BALB/c mouse. B-1 cells are involved in fighting C. neoformans infection, also due to their production of natural IgM antibodies against the yeast capsular content, while B-2 cells could act in the production of antigen-specific IgG antibodies 22 , 67 , so B-1 cells ends up being responsible for a large part of IgM in the early stages of C. gattii , and therefore, as we reveled, this amount was compromised in the XID mice.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, our data also highlight an important role of the B-1 cells during chronic infection, as seen by the higher IgM antibody titer compared with the antigen-specific IgG antibody titer between the XID and BALB/c mouse. B-1 cells are involved in fighting C. neoformans infection, also due to their production of natural IgM antibodies against the yeast capsular content, while B-2 cells could act in the production of antigen-specific IgG antibodies 22 , 67 , so B-1 cells ends up being responsible for a large part of IgM in the early stages of C. gattii , and therefore, as we reveled, this amount was compromised in the XID mice.…”
Section: Discussionmentioning
confidence: 65%
“…The role of hypogammaglobulinemia in our patient also played an essential role in increasing the risk of infection. In vitro studies have demonstrated that human IgM and immunoglobulin G (IgG) change the morphology of C. neoformans and that IgM inhibits titian-like cell formation, which can reduce virulence and the risk of disseminated disease [ 35 ] . Previous reports have described an association between hypogammaglobulinemia and increased risk for cryptococcal disease, including in HIV-infected patients [ 6 , 36–38 ] .…”
Section: Discussionmentioning
confidence: 99%
“…X-linked hyper-IgM immunodeficiency syndrome is caused by mutations that occur in the CD40 ligand gene which results in decreased levels of IgG and IgA and elevated IgM has been shown to increase susceptibility to infections including invasive and cutaneous cryptococcosis particularly observed in pediatric male patients [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 ]. In addition, in vitro assays using C. neoformans found that IgM but not IgG inhibited Titan cell formation, reduced capsule thickness, and decreased the expression of chitin synthetase genes ( CHS1 , CHS2 , CHS8 , α-1–3-glucan synthetase ( AGS1 ), and β-1,3-glucan synthetase ( FKS1 ) [ 156 ]. Furthermore, IgM reduced the expression of the stress response pathways RIM101 and HOG1 [ 156 ].…”
Section: Associations Between Human Attributes and Cryptococcosismentioning
confidence: 99%
“…In addition, in vitro assays using C. neoformans found that IgM but not IgG inhibited Titan cell formation, reduced capsule thickness, and decreased the expression of chitin synthetase genes ( CHS1 , CHS2 , CHS8 , α-1–3-glucan synthetase ( AGS1 ), and β-1,3-glucan synthetase ( FKS1 ) [ 156 ]. Furthermore, IgM reduced the expression of the stress response pathways RIM101 and HOG1 [ 156 ]. There have been several studies suggesting a link with polymorphism in the Fc-gamma receptors of immunoglobulin genes and cryptococcosis [ 157 , 158 , 159 ].…”
Section: Associations Between Human Attributes and Cryptococcosismentioning
confidence: 99%